2015
DOI: 10.1016/j.jvs.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Examination of factors in type I endoleak development after thoracic endovascular repair

Abstract: Endoleak risk seems not to be increased by an emergency setting. However, the relatively high rate of late endoleak observed after emergent TAA repair advocates for close follow-up, contrary to traumatic aortic rupture. Furthermore, regardless of the pathologic process, a longer proximal landing zone is likely to guarantee early and late success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 28 publications
0
34
1
Order By: Relevance
“…44,52 The most common causes of type Ia endoleak are malapposition of the proximal segment of the stent-graft, mainly due to short proximal landing zone and severe angulation. 84,85 To prevent malapposition, oversizing in TBAD should not be greater than 20% to reduce the risk of proximal neck dilatation. 86 Another recent study showed that immediate type Ia endoleak was related to larger preoperative distal FL area (498±274 vs 284±213 mm 2 , p=0.02) and distal aortic area (759±275 vs 624±185 mm 2 , p=0.03).…”
Section: Endoleakmentioning
confidence: 99%
“…44,52 The most common causes of type Ia endoleak are malapposition of the proximal segment of the stent-graft, mainly due to short proximal landing zone and severe angulation. 84,85 To prevent malapposition, oversizing in TBAD should not be greater than 20% to reduce the risk of proximal neck dilatation. 86 Another recent study showed that immediate type Ia endoleak was related to larger preoperative distal FL area (498±274 vs 284±213 mm 2 , p=0.02) and distal aortic area (759±275 vs 624±185 mm 2 , p=0.03).…”
Section: Endoleakmentioning
confidence: 99%
“…This raises new issues relating to the optimal LZ, whose quality and stability largely determines the technical success of the procedure. 1 These developments have led to the concept of conformability, which implies adequacy of contact between material and LZ, independently of anatomic characteristics, taking into account that LZ length can vary from brand to brand (15 to 20 mm). However, clinical experience has shown that in terms of conformability the material has certain limits when morphology is defined as complex.…”
Section: Introductionmentioning
confidence: 99%
“…7,9,13 Hostile necks and inhomogeneous landing zones make planning, device selection, and especially implanting of the grafts quite challenging. 14, [16][17][18] Zone 1 repair showed a high primary type Ia endoleak rate of 15% in our series. Zone 2 repair was more effective in proximal sealing (primary type Ia endoleak, 4%), with comparable technical success rates as published for zone 0.…”
Section: Discussionmentioning
confidence: 45%
“…2,6,7,13 On the other hand, hemiarch repair has a significant risk of technical failure, especially for zone 1, by development of primary type Ia endoleak. 7,9,[15][16][17][18] Published data are mainly available on comparison of zone 0 vs zone 1, whereas data on zone 2 repair were mostly excluded from analysis. 4,13 Hence, there is little knowledge for rating hemiarch repair for zone 2 in shortand long-term outcome compared with more extended reconstruction types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation